Análisis de las consecuencias jurídicas del incumplimiento de los contratos de promesa de compra venta de bienes inmuebles celebrados en la notaría quinta del Cantón Ibarra en el periodo 2021-2022 - Flores Flores, Jhosuan Israel (2023)
The present investigation about the legal consequences of the breach of the contract of promise to buy and sell real estate had as its main objective the regulatory, doctrinal and jurisprudential study about this object of study. Regarding the state of the art, it was possible to find that the problem about the legal uncertainty that this contract entails, has specific causes that have been investigated in different ways. The methodology used in this study was qualitative, since the method that was obtained was the legal partner, which explains from the doctrine, the phenomenon that occurred in the daily life of citizens, in this case of the purchase and sale of real estate. The techniques that were used were: the documentary technique, which served as the basis for the compilation of the existing regulations: Constitution, Civil Code and Notarial Law, also for the review and analysis of the doctrine and jurisprudence found in the digital repositories. In addition, the technique of interviewing experts such as: notaries, judges and lawyers was used, who nurtured the study from their expertise in the labor field. The most important results that were acquired were reference to the regulatory framework, and the lack of specificity about articles on the promise contract in the Civil Code. And among the most relevant conclusions of the study, it can be indicated that the purchase-sale promise contracts are elaborated without rigor by the lawyers, for which, a posteriori, they present inconveniences in their compliance, as well as the lack of information that have the contracting parties regarding the legal consequences of failure to meet deadlines, and the contract.